Cystic Lymphangioma of the Pancreas: Diagnostic and Therapeutic Challenges - Fahimi, Hossein; Faridi, Maziar; Gholamin, Seemin; Molanaee, Sharareh; Khorsandi, Maziar (JOP. Journal of the Pancreas, 2010)
Context Cystic lymphangiomas originate as benign masses which occur mostly in children especially in the head and neck region and/or the groin. Although abdominal lymphangiomas are rare, they are most commonly reported in adults. In addition, pancreatic involvement is rare. Lymphatic malformation with blockage of the lymphatic flow is the most common etiology leading to the formation of lymphangiomas. Cystic lymphangiomas should always be included in the differential diagnosis of abdominal masses which present with mass effect signs and symptoms. Due to its rarity, it forms a diagnostic and therapeutic challenge for the clinician. Case report We herein report the case of a 43-year-old man with a cystic lymphangioma detected in the head of the pancreas and describe the surgical procedure utilized as the therapeutic medium. Conclusion To remove this mass, we utilized a modified approach to a classic pancreaticoduodenectomy. This technique involved resection of the head of the pancreas while preserving the upper 2nd portion of the duodenum and the ampulla of Vater. The result of our 30-month follow-up of this patient has been very satisfactory with no complications. Image: A schematic presentation of the cystic mass.